Design and evaluation of matrix base with sigmoidal release profile for colon-specific delivery using a combination of Eudragit and non-ionic cellulose ether polymers - Asghar, Laila Fatima Ali; Chandran, Sajeev (Drug delivery and translational research, 2011)
A pH- and time-controlled drug delivery system with sigmoidal release profile was developed using Eudragit (L100 or S100) in combination with hydroxy ethyl cellulose (HEC) or hydroxy propyl cellulose (HPC) for sigmoidal release of indomethacin in the potential treatment of colon cancer. The effect of varying proportions of polymer type on sigmoidal release was evaluated. The prepared tablets were also characterized for physical characteristics, in vitro drug release, release kinetics, and stability on storage. The gastrointestinal transit of formulations was also investigated in human subjects. Results from in vitro release studies indicated that due to the presence of pH-responsive polymers, a pH- and time-dependent release pattern was observed, which was characterized by negligible drug release in first 4–6 h followed by controlled release for 14–16 h in alkaline pH. In vivo studies indicated that HPC-based formulations had satisfactory matrix strength to withstand gastric and colonic transit, while HEC-based tablets disintegrated during transit through the small intestine. All the formulations were stable on storage. It was concluded that such a matrix design has good potential for drug delivery to colon with controlled release.